2022
DOI: 10.1155/2022/9664078
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of the Syndrome-Position Point Selection Method on Idiopathic Tinnitus of Phlegm-Fire Stagnation Pattern: A Randomized Controlled Study

Abstract: Objective. To investigate the clinical effect of the syndrome-position point selection method on the intervention of idiopathic tinnitus of the phlegm-fire stagnation pattern. Methods. One hundred patients with idiopathic tinnitus of phlegm-fire stagnation pattern who met the inclusion criteria were randomized into the treatment group and the control group by the random number table method, with 50 cases in each group. The treatment group (syndrome-position point selection method) was treated with acupuncture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…First, it only included studies published before November 2017. A few RCTs [36][37][38] have been published since the publication of the previous NMA study to further investigate the efficacy and safety of acupuncture for alleviating primary tinnitus. In order to determine the most recent evidence, it is crucial to include the results of recent clinical trials in an updated systematic review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it only included studies published before November 2017. A few RCTs [36][37][38] have been published since the publication of the previous NMA study to further investigate the efficacy and safety of acupuncture for alleviating primary tinnitus. In order to determine the most recent evidence, it is crucial to include the results of recent clinical trials in an updated systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…35 As a result, our study will undertake the most comprehensive and up-to-date literature search, including more eligible RCTs published between 2018 and 2023. [36][37][38] In addition, our study will improve the establishment of PICOS by incorporating more rigorous but feasible inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its green therapy and safety, it is recognized by more and more people. Acupuncture at the acupoints near the ear can accelerate the microcirculation of the inner ear, [ 8 ] improve the permeability of the capillaries in the ear, prevent or reduce the necrosis of the inner ear spiral organ hair cells, and improve the function of the cochlea. [ 9 ] Studies have found that acupuncture treatment of idiopathic tinnitus has a certain therapeutic advantage, is an important treatment.…”
Section: Introductionmentioning
confidence: 99%
“…"Lifting and thrusting" is a common technique of traditional needle acupuncture, which plays an important role in acupuncture treatment [8][9][10][11][12][13][14][15][16]. Researchers have tried to simulate the lifting-and-thrusting technique in laser acupuncture to improve its efcacy [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%